Stress-assisted thermal diffusion barrier breakdown in ion beam deposited Cu/W nano-multilayers on Si substrate observed by in Situ GISAXS and transmission EDX - Romano Brandt, L; Salvati, E; Wermeille, D; Papadaki, C; Le Bourhis, E; Korsunsky, AM (American Chemical Society, 2021)
The thermal stability of Cu/W nano-multilayers deposited on a Si substrate using ion beam deposition was analyzed in situ by GISAXS and transmission EDX—a combination of methods permitting the observation of diffusion processes within buried layers. Further supporting techniques such as XRR, TEM, WAXS, and AFM were employed to develop an extensive microstructural understanding of the multilayer before and during heating. It was found that the pronounced in-plane compressive residual stress and defect population induced by ion beam deposition result in low thermal stability driven by thermally activated self-interstitial and vacancy diffusion, ultimately leading to complete degradation of the layered structure at moderate temperatures. The formation of Cu protrusions was observed, and a model was formulated for stress-assisted Cu diffusion driven by Coble creep along W grain boundaries, along with the interaction with Si substrate, which showed excellent agreement with the observed experimental data. The model provided the explanation for the experimentally observed strong correlation between thin film deposition conditions, microstructural properties, and low thermal stability that can be applied to other multilayer systems.